Legal Protection for Nurses in Pharmaceutical Services Where there are No Pharmaceutical Staffs at the Community Health Center - Rizka Dianita; Retno Ariani; Swabawa Wicaksana; Mokhamad Khoirul Huda (Institute of Medico-legal Publications Pvt Ltd, 2021)
Puskesmas is a first-level healthcare service facility that organizes health efforts prioritized promotive andpreventive actions. In executing its health efforts, puskesmas must take actions according to standards,including in pharmaceutical services. It will be different when the pharmacy service is provided by nursesinstead of provided by pharmacy staffs. Following the prevailing law in Indonesia today, nurses’ authority incarrying out their pharmacy duties in practice is only limited. To provide assurance and legal protection fornurses in performing pharmaceutical services in health centres where there are no pharmacists/pharmaceuticaltechnical staff, laws and regulations related to nursing protection have an essential function. It also protectsnurses to avoid criminalization of nurses by law enforcement officials.